Role of Biometric security for The Enhancement of Data Security - Gupta, Himanshu; Chauhan, Kapil (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
In today's society, data security is the big problem for every business organization or an individual. Most found threat is theft of personal data and information. With time digital data become more prevalent, personnel try to secure their information by using highly encrypted passwords and authentication identities, but, the misuse and theft of these security measures are rising in lot of theft cases Taking advantage of security flaws in authentication identities ends up in cards being duplicated or counterfeited and hence misused. This increasing fight with cyber security has been the sole reason of making biometric security systems, the important area of concern is that how do one can implement the biometric security for increasing of data security. First unique feature which is found different in every human is Fingerprints; Humans have used fingerprints for personal identification. Presently, most of the organisation use fingerprint recognition for authentication process it is one of the oldest and most commonly used biometrics, with high accuracy & generally easy and efficient and fast. In this paper we propose the idea to use fingerprint recognition along with the user authentication password or to access the data or information. Since the only person who can access information is the person linked to it, no thief can gain access. It also makes your data, very hard for cyber criminals to hack into.